Incorporation of supramolecular polymer-functionalized graphene: Towards the development of bio-based high electrically conductive polymeric nanocomposites. (18th August 2017) - Cheng, Chih-Chia; Liao, Zhi-Sheng; Huang, Jyun-Jie; Huang, Shan-You; Fan, Wen-Lu
Abstract: Supramolecular polymer-functionalized graphene (SPFG), a combination of exfoliated graphite nanoplatelets and a low-molecular-weight supramolecular polymer, can be incorporated into poly( L -lactic acid) (PLLA) matrices for efficient production of SPFG/PLLA composites; SPFG behaves as a highly efficient reinforcing material and substantially improves the overall physical properties compared to commercial PLLA. The SPFG content of the PLLA composites can be readily adjusted to obtain the desired composite products with specific crystallization and mechanical characteristics. At the optimized blending ratio of 10 wt% SPFG and 90 wt% PLLA, the resulting film exhibited a 65.2% lower oxygen permeation rate and two-fold higher ultimate tensile strength (47.8 MPa) than pristine PLLA. More excitingly, this newly-developed composite possessed superior electrical conductivity of up to 9.58 × 10 −3 S/cm at a SPFG loading of 10.0 wt%, which was nearly four orders of magnitude higher than control graphite/PLLA composites at the same nanofiller content. Thus, SPFG provides a potential route towards the development of high performance graphene-based PLLA nanocomposites for a broad range of electronic and biomedical applications. Graphical abstract: Supramolecular polymer-functionalized graphene acts as a highly efficient reinforcing material that could be employed to substantially improve the overall performance of bio-based polymer composites.